Enhanced tensile ductility of tungsten microwires via high-density dislocations and reduced grain boundaries. (30th December 2021) - Dang, Chaoqun; Lin, Weitong; Meng, Fanling; Zhang, Hongti; Fan, Sufeng; Li, Xiaocui; Cao, Ke; Yang, Haokun; Zhou, Wenzhao; Fan, Zhengjie; Kai, Ji-jung; Lu, Yang
Highlights: W microwires with designed microstructure were microfabricated under EBSD guidance. High-density dislocations were introduced in W with reduced grain boundaries. Ultrahigh strength and ductility were achieved in engineered W microwires. The motion of pre-existing high-density dislocations produces high ductility of W. Abstract: Despite being strong with many outstanding physical properties, tungsten is inherently brittle at room temperature, restricting its structural and functional applications at small scales. Here, a facile strategy has been adopted, to introduce high-density dislocations while reducing grain boundaries, through electron backscatter diffraction (EBSD)-guided microfabrication of cold-drawn bulk tungsten wires. The designed tungsten microwire attains an ultralarge uniform tensile elongation of 10.6%, while retains a high yield strength of 2.4 GPa. in situ TEM tensile testing reveals that the large uniform elongation of tungsten microwires originates from the motion of pre-existing high-density dislocations, while the subsequent ductile fracture is attributed to crack-tip plasticity and the inhibition of grain boundary cracking. This work demonstrates the application potential of tungsten microcomponents with superior ductility and workability for micro/nanoscale mechanical, electronic, and energy systems. Graphical Abstract: Image, graphical abstract